ПІДХОДИ ДО ІДЕНТИФІКАЦІЇ СТРАХОВИХ ГРУП - Біла, Дарина Валеріївна (Науковий журнал «Світ фінансів», 2017)
Біла Д. В. Підходи до ідентифікації страхових груп. Досліджена зарубіжна практика ідентифікації страхових груп, передумови виокремлення IAIS поняття “міжнародна страхова група” та перелік критеріїв для проведення ідентифікації страхової групи. Розглянуто підходи до утворення фінансових груп. Проаналізовано активність страхових груп на ринку України та розкрито їх склад. Наведено недоліки розробленого Нацкомфінпослуг підходу до віднесення компаній до небанківських фінансових груп, запропоновано доповнення до ідентифікаційних ознак та пропозиції щодо забезпечення інформаційної прозорості діяльності страхових груп. Белая Д. В. Подходы к идентификации страховых групп. Исследованы зарубежные практики идентификации страховых групп, предпосылки выделения IAIS понятие “международная страховая группа” и перечень критериев для проведения идентификации страховой группы. Рассмотрены подходы к созданию финансовых групп. Проанализирована активность страховых групп на рынке Украины и раскрыт их состав. Приведены недостатки разработанного Нацкомфинуслуг подхода к отнесению компаний к небанковским финансовым группам, предложены дополнения к идентификационным признакам и предложения по обеспечению информационной прозрачности деятельности страховых групп. Bila D. Approaches to identifying insurance groups. Introduction. The insurance group existence in the market and risks that are associated with insurance groups’ activities are led to the urgency of scientific research and determining the approaches to identify the insurance groups in Ukraine.Purpose. To study the international experience and national practice of the insurance groups identification and the insurance groups’ impact estimation on the insurance market.Results. The article analyzes the foreign practice of the insurance groups identification, the background of the IAIS emphasize the concept of “international insurance group” and the list of the insurance group identification criteria. The author examined the financial group creation ap-proaches: permissive, mixed, separate; and the insurance group identity indicators in Ukraine that are adopted by the NationalCommission for the Financial Service Markets Regulation of Ukraine. Author revealed the presence of insurance groups in the domestic insurance market that are controlled by international financial conglomerates; analyzed the insurance groups’ activity in Ukrainian market and studied their composition. The article contains the list of the insurance group performance indicators that are provided by the regulator; discloses the approach drawbacks that is developed by the National Commission for the Financial Service Markets Regulation for classifying companies as non-bank financial groups. Conclusion. The author formed the proposals that are aimed at improving transparency in the insurance market of Ukraine, such as: publication of information about the implementation of non-bank financial group of the regulatory requirements for regulatory capital adequacy. The article illuminates the financial performance indicators information of non-bank financial groups.